Dosing feasibility and tolerability of intranasal diazepam in adults with epilepsy. Issue 10 (25th August 2014) - Sperling, Michael R.; Haas, Kevin F.; Krauss, Gregory; Seif Eddeine, Hussam; Henney, Herbert R.; Rabinowicz, Adrian L.; Bream, Gary; Squillacote, David; Carrazana, Enrique J.
Summary Objective To determine the feasibility of administering a diazepam nasal spray formulation (diazepam‐NS) to adults with epilepsy during a generalized tonic–clonic seizure or in the postictal period following a tonic–clonic or other seizure type, to assess pharmacokinetics and to assess tolerability. Methods An open‐label study was conducted in patients admitted to the epilepsy monitoring unit. Eligible patients received a single dose of diazepam‐NS approximating 0.2 mg/kg. Plasma diazepam concentrations were measured serially up to 12 h postdose, and maximum observed plasma concentration (Cmax); time to maximum concentration (Tmax); and the area under the plasma concentration–time curve for time zero to last sampling time (AUC0–12) were estimated and dose‐normalized. Pharmacodynamic assessments included Kaplan‐Meier analysis to determine the time‐to‐next seizure. Safety and tolerability were assessed. Results Of the 78 patients who consented, 30 had treatment and pharmacokinetic data. Ten patients were treated during a convulsive tonic–clonic seizure, seven within 5 min following the last clonic jerk, and 13 in the postictal period ≥5 min after a tonic–clonic or following other seizure‐types. Diazepam median Tmax was 45 min. Dose‐normalized mean Cmax and AUC0–12 values of diazepam were comparable among patients regardless of the timing of diazepam‐NS administration in relation to seizure. Of those treated, 65% were seizure‐free during the 12‐h observation period and 35% had post‐dose seizures. Treatment was well tolerated, with no unexpected safety findings: 74% had mild and 25% had moderate adverse events. Nasopharyngeal signs were resolved by 12 h postdose. Significance Diazepam can be delivered in effective therapeutic concentrations by a nasal spray device during the convulsive phase of tonic–clonic seizures or in the postictal periods following tonic–clonic or other seizure types.